A Research on Relationship of Institutionalization and Institutional Entrepreneurship - Sanal, Musa; Efeoglu, İbrahim Efe (International Review of Management and Marketing, 2013)
Institutionalization is a dynamic process which is developed as a result of enterprise sensitivity to the environmental transformation and consists of its efforts to conformity to this transformation. Institutional entrepreneurship, however, is the process of building a different constitution inside the enterprise to induce entrepreneurial spirit and to lead the association into transformation and modernism. These two notions can be seen as the activities that will achieve the permanency and the efficiency of family businesses which have a big interest in world economics. In this study, the components of the institutionalization are; social responsibility and professionalization, institutional entrepreneurship components are aimed to be measured on the basis of the risk and proactivity and the modernism in the family businesses which are sampling units. In this study, the deduced survey hypothesis are tested using the statistical analysis data, and the contribution of the study to the association is discussed in the light of derived findings and evaluations, also a set of suggestions which can enlighten the way for next studies are developed and how the business world will profit from this study is emphasized. Keywords: Family Businesses; Small and Medium Sized Company; Institutionalization; Institutional Entrepreneurship JEL Classifications: MOO; L26